Polysemous Tradition as a Common Basis for Ideological Resistance in Windsor Forest and The Communist Manifesto (Groundings Undergraduate, 2024)
This paper delves into the nuanced use of tradition as a foundation for ideological resistance in Alexander Pope’s “Windsor Forest” and Karl Marx and Friedrich Engels’ “The Communist Manifesto.” Despite their divergent contexts—Pope’s text emerging from early 18th-century England and the Manifesto from mid-19th-century industrializing Europe—both works leverage historical and literary traditions to critique and resist dominant ideologies of their times. “Windsor Forest” subtly confronts ideologies of Protestant ascendancy and anti-Catholic sentiment prevalent in England following the Glorious Revolution of 1688, promoting peace and the unity of Great Britain under Queen Anne’s Stuart monarchy as alternatives to war and division. Through literary devices such as allegory and panegyric, Pope employs tradition not only to question the contemporary political and social landscape but to posit the Stuart dynasty as a symbol of national prosperity and harmony.Contrastingly, “The Communist Manifesto” openly challenges the capitalist ideology that Marx and Engels argue perpetuates class struggle and exploitation of the proletariat. The Manifesto calls for a revolutionary overhaul of the social order, drawing on traditions of socialist thought and the historical precedent of class struggle to justify its radical aims. Despite its revolutionary stance, the Manifesto similarly relies on the manipulation of tradition—both embracing and rejecting it—to articulate a vision of communist society.Both texts, therefore, are situated at the intersection of literary expression and ideological conflict, illustrating how tradition can serve as a versatile tool in the articulation of resistance. Whether through the invocation of historical continuity and national identity in “Windsor Forest” or the revolutionary call to arms in “The Communist Manifesto,” tradition is employed to critique existing social and political orders. The abstract underscores the complexity of these texts’ engagement with tradition, highlighting their shared emphasis on the transformative potential of ideological resistance. This comparison illuminates the rich dialogues between literature and politics, demonstrating how textual analysis can reveal deeper insights into the mechanisms of ideological critique and resistance.
Keywords: Windsor Forest; Alexander Pope; Communist Manifesto; Karl Marx; Friedrich Engels; Tradition; Ideological Resistance; Political History